Conceptional design of nano-particulate ITO inks for inkjet printing of electron devices - Kölpin, Nadja; Wegener, Carsten Moritz; Teuber, Erik; Polster, Sebastian; Frey, Lothar; Roosen, Andreas (Journal of Materials Science, 2013)
This manuscript presents the conceptional design of indium tin oxide inkjet inks for the manufacture of electron devices. For this purpose, the process window of the printer used is identified and the inks are conceived to meet the requirements. The nano-particles are effectively stabilized in different dispersion media. The rheological, the wetting and the drying behavior of the inks are adapted to the inkjet process and the substrates to be coated. To assemble a field effect transistor (FET), the most suitable ink is chosen and source and drain contacts are printed. In the device, a nano-particulate ZnO layer acts as semiconducting layer and the gate electrode as well as the dielectric layer is formed by a thermally oxidized silicon wafer. The electron device assembled shows the typical FET characteristic proving its functionality. © 2012 Springer Science+Business Media New York.

Electromagnetic analysis of conductor track surface roughnesses from 1 GHz to 110 GHz - Talai, Armin; Gmeiner, Björn; Wegener, Carsten Moritz; Roosen, Andreas; Kölpin, Alexander; Steinhäußer, Frank; Deisinger, Ulrike; Bittner, Achim; Schmid, Ulrich; Weigel, Robert (Electromagnetics in Advanced Applications (ICEAA), 2014 International Conference on, 2014)
Conductor tracks comprise a frequency dependent attenuation of electromagnetic waves, since with increasing frequency the current flow is displaced to the near surface region due to the skin effect. Therefore, the effective length of the conductor is increased by the surface roughness, while its effective cross-section is decreased by current displacement, both leading to higher metallization loss. In this paper, surface topographies of typical conductor materials were recorded by confocal microscopy and rebuilt as 3D CAD models. Subsequent electromagnetic simulations reveal the influence due to roughness on high frequency characteristics for physical vapor deposited, thick film and photochemically etched microstrips.
UnivIS-Import:2015-04-17:Pub.2014.tech.IMMD.lsinfs.electr

Flexographic printing of nanoparticulate tin-doped indium oxide inks on PET foils and glass substrates - Wegener, Carsten Moritz; Spiehl, Dieter; Sauer, Hans Martin; Mikschl, Florian; Liu, Xinxin; Kölpin, Nadja; Schmidt, Michael; Jank, Michael; Dörsam, Edgar; Roosen, Andreas (Journal of Materials Science, 2016)
This contribution deals with flexographic printing of nanoparticulate tin-doped indium oxide (ITO) inks for the manufacture of fine lines on PET foils and glass substrates. The development and optimization of ITO inks, based on solutions of water and ethanol, for the flexographic printing process is presented. The influence of the solvent composition, of the particle content, and of the molar mass of the binder polyvinylpyrrolidone on the printing result is shown. ITO lines with a minimum line width of around 120 µm were printed using a printing plate with a feature size of 50 µm; the ITO lines exhibited a thickness of around 1 µm. Laser post-treatment was used to consolidate the top layer of the nanoparticulate ITO structures resulting in improved electrical properties; low sheet resistance values of around 300 Ω/□ were achieve

Gelation of polyvinylbutyral solutions by the addition of tetrabutyl orthotitanate - Wegener, Carsten Moritz; Kaschta, Joachim; Münstedt, Helmut; Roosen, Andreas (Rheologica Acta, 2014)
This paper discusses the gelation of polyvinylbutyral (PVB) solutions by the addition of tetrabutyl orthotitanate. The addition of around 0.10 vol.% tetrabutyl orthotitanate to an ethanol-based PVB solution already causes a pronounced gelation. For the characterization of this gelation reaction, different rheological measurements are used. The characterization is mainly performed in the linear viscoelastic regime. Time sweeps prove the stability of the samples during the measuring time. Frequency sweeps are used to investigate the state of gelation after different reaction times as well as the dependence of the degree of the gelation on the tetrabutyl orthotitanate concentration. Furthermore, the gelation point is determined by measuring the loss factor tan delta as a function of frequency. A strong influence of water on the degree of gelation is shown; by the addition of different amounts of water, the gelation can be controlled or even avoided. Amplitude sweeps reveal the breakdown of certain network structures at high amplitudes which recover after the strain is lowered.
Keywords: Polyvinylbutyral (PVB); Gelation with titanate; Dynamic mechanical analysis (DMA); Network characterization; Gel point

Materials Integration for Printed Zinc Oxide Thin-Film Transistors: Engineering of a Fully-Printed Semiconductor/Contact Scheme - Liu, XinXin; Wegener, Carsten Moritz; Polster, Sebastian; Jank, Michael; Roosen, Andreas; Frey, Lothar (Journal of Display Technology, 2016)
We report for the first time on the impact of a printed indium tin oxide (ITO) layer inserted between a printed silver conductor and solution processed zinc oxide (ZnO) leading to an optimized semiconductor/contact scheme for full print integration. Introducing the ITO interlayer, the contact resistance is reduced by two orders of magnitude. Nanoparticle thin-film transistors (TFTs) in this Ag/ITO contact configuration show improved saturation mobility of 0.53 cm(2) . V-1 . s(-1) with respect to 0.08 cm(2) . V-1 . s(-1) without ITO interlayer. The contact improvement can be attributed to either an increased charge carrier concentration or a reduction of band offsets at the ZnO/electrode interface.
Keywords: Contact resistance; indium-tin-oxide; thin-film transistors (TFTs); zinc oxide (ZnO)

Printing of Ultrathin Nanoparticulate Indium Tin Oxide Structures - Wegener, Carsten Moritz; Spiehl, Dieter; Mikschl, Florian; Liu, Xinxin; Roosen, Andreas (International Conference and Exhibition on Ceramic Interconnect and Ceramic Microsystems Technologies (CICMT), 2015)

PVP a binder for the manufacture of ultrathin ITO/polymer nanocomposite films with improved electrical conductivity - Wegener, Carsten Moritz; Kato, Minato; Kakimoto, Ken-Ichi; Spallek, Stefanie; Spiecker, Erdmann; Roosen, Andreas (Journal of Materials Science, 2015)
This paper presents the manufacture of ultrathin (< 1 A mu m) transparent conductive indium tin oxide (ITO) films based on nanoparticulate ITO slurries by the profile rod technique using the binder polyvinyl pyrrolidone (PVP) as an organic additive. The influence of the slurry composition on the film thickness and the specific electrical resistance as well as the transmission of the dried films is evaluated. The organic solvent ethanol and different types of the PVP binder were tested for slurry preparation and layer performance. ITO green films with low specific electrical resistance of 3 Omega cm, 87 % inline transmission, and layer thicknesses of only 250 nm could be manufactured. Furthermore, the influence of heat treatments up to 400 A degrees C on the electrical properties of the ITO films was evaluated.